Keseimbangan Jiwa dan Akal dalam Filsafat Pendidikan Agama Islam Perspektif Buya Hamka - Farah Nur Fadhilah; Munir; Ismail (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Islamic education plays a strategic role in shaping holistic human beings by integrating intellectual, spiritual, and moral development. However, contemporary educational practices tend to emphasize cognitive achievement while neglecting the cultivation of the soul and character, which contributes to moral decline and mental health issues among students. This study aims to examine the concept of balance between soul (nafs) and intellect (‘aql) in Buya Hamka’s philosophy of Islamic education and its relevance to contemporary educational challenges. This research employs a qualitative descriptive approach using library research. Primary data are derived from Buya Hamka’s works, such as Tasawuf Modern and Falsafah Hidup, while secondary data are obtained from relevant scholarly literature. Data were analyzed through thematic analysis, including data reduction, theme classification, and interpretative analysis. The findings reveal that, according to Buya Hamka, ideal Islamic education must integrate intellectual development with spiritual and moral cultivation to achieve mental well-being, inner peace, and moral resilience. This concept is highly relevant to modern Islamic education, as it offers a holistic framework for integrating intellectual, emotional, and spiritual intelligence in developing morally grounded and resilient learners.